Infinite Summation + Infinite Products

Calculus Level 5

n = 1 k = n + 1 ( 1 ( n k ) 2 ) \large\displaystyle\sum_{n=1}^{\infty}\prod_{k=n+1}^{\infty}\left(1-\left(\dfrac{n}k\right)^2\right) Let S S denote the value of series above. If S = A B + C π D B S=\dfrac{A}{B}+\dfrac{C\pi}{D\sqrt{B}} where A , B , C A,B,C and D D are coprime positive integers. Find the value of A + B + C + D A+B+C+D .


The answer is 15.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
Jul 15, 2015

n = 1 k = n + 1 ( 1 ( n k ) 2 ) = n = 1 k = n + 1 k 2 n 2 k 2 = n = 1 k = n + 1 ( k + n ) ( k n ) k 2 = n = 1 j = 1 ( 2 n + j ) j ( n + j ) 2 = n = 1 lim m j = 1 m ( 2 n + j ) j ( n + j ) 2 = n = 1 lim m m ! ( 2 n + m ) ! ( n ! ) 2 ( 2 n ) ! [ ( n + m ) ! ] 2 = n = 1 ( n ! ) 2 ( 2 n ) ! = n = 1 1 ( 2 n n ) = 1 3 + 2 π 9 3 [ See Note ] \begin{aligned} \sum_{n=1}^\infty \prod_{k=n+1}^\infty \left(1 - \left(\frac{n}{k}\right)^2 \right) & = \sum_{n=1}^\infty \prod _{k=n+1} ^\infty \frac{k^2 - n^2}{k^2} \\ & = \sum_{n=1}^\infty \prod _{k=n+1} ^\infty \frac{(k+n)(k-n)}{k^2} \\ & = \sum_{n=1}^\infty \prod _{j=1} ^\infty \frac{(2n+j)j}{(n+j)^2} \\ & = \sum_{n=1}^\infty \lim_{m \to \infty} \prod _{j=1} ^m \frac{(2n+j)j}{(n+j)^2} \\ & = \sum_{n=1}^\infty \lim_{m \to \infty} \frac{m!(2n+m)!(n!)^2}{(2n)![(n+m)!]^2} \\ & = \sum_{n=1}^\infty \frac{(n!)^2}{(2n)!} \\ & = \sum_{n=1}^\infty \frac{1}{\begin{pmatrix} 2n \\ n \end{pmatrix}} = \frac{1}{3} + \frac{2\pi}{9\sqrt{3}} \quad \color{#D61F06}{[\text{See Note}]} \end{aligned}

A + B + C + D = 1 + 3 + 2 + 9 = 15 \Rightarrow A+B+C+D = 1+3+2+9 = \boxed{15}

Note: \color{#D61F06}{\text{Note: }} See (37)

Nice easy problem! Did the same!

Kartik Sharma - 5 years, 11 months ago

Log in to reply

The Note: \color{#D61F06}{\text{Note: }} See (37) part is from Euler. I read about it for the first time. I was trying to solve it but couldn't.

Chew-Seong Cheong - 5 years, 11 months ago

Log in to reply

You can use Beta function, by what I mean that you can transform that term to integral form using Beta function and then it comes out right, I guess.

Kartik Sharma - 5 years, 11 months ago

Log in to reply

@Kartik Sharma I did try with Beta, but maybe not hard enough.

Chew-Seong Cheong - 5 years, 11 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...